Comparison of Transradial and Transfemoral Access for Coronary Bypass Graft Angiography - Rohit Seth Loomba; Saurabh Aggarwal; Navdeep Gupta; Arun Kanmanthareddy; Imtiaz Ismail; Anushree Agarwal; Karan Nijhawan; Gaurav Aggarwal; Rohit Arora; Marcelo SanMartin; Richard Anderson (Annals of Circulation - Peertechz Publications, 2017)
Introduction: Transradial access has been shown to be safe and effective in the setting of percutaneous coronary intervention (PCI) and even being benefi cial in regards to vascular complications and perceived quality of life after the intervention. However, data is limited in patients having previously undergone coronary artery bypass grafting (CABG) where procedural complexity can be increased. Methods: Studies comparing transradial and transfemoral access for PCI in patients having undergone CABG were identifi ed. Data for similar endpoints was extracted for subsequent meta-analysis. Bias and heterogeneity were also assessed. Results: There was no significant difference in procedure success (OR 0.87, 95% CI 0.43 to 1.73, p=0.68), procedure time (MD 231.98 seconds, 95% CI -84.39 to 548.36, p=0.15), fl uoroscopy time (MD 51.75 seconds, 95% CI -66.83 to 170.34, p=0.39), contrast volume (MD 1.67 milliliter, 95% CI -22.16 to 25.49, p = 0.89) and in-hospital mortality (OR 0.50, 95% CI 0.13 to 1.92, p=0.31) between those in the transradial and transfemoral access groups. Transradial access was associated with fewer vascular complications (OR 0.33, 95% CI 0.16 to 0.72, p=0.005). Conclusions: Transradial access for PCI in patients with prior CABG is safe, with fewer vascular complications, and offers an effective and potentially favorable alternative to transfemoral access. Condensed abstract: Transradial access has been demonstrated to offer benefi ts in comparison to transfemoral access for percutaneous coronary intervention (PCI). This advantage has not been fully elucidated for PCI of coronary artery bypass grafts (CABG). A meta-analysis was conducted to study the two access options and found that transradial access for PCI of CABG grafts is safe and may in fact be associated with fewer vascular complications.